Glacitectonism, subglacial and glacilacustrine processes during a Neoproterozoic panglaciation, north‐east Svalbard. Issue 2 (7th February 2016) - Fleming, Edward J.; Benn, Douglas I.; Stevenson, Carl T. E.; Petronis, Michael S.; Hambrey, Michael J.; Fairchild, Ian J.
Abstract: Palaeoenvironmental reconstruction of Neoproterozoic successions has been the subject of long‐standing debate, particularly concerning the interpretation of diamictites. The Wilsonbreen Formation of north‐east Svalbard is a 130 to 180 m thick diamictite‐dominated glacigenic succession deposited during a late Cryogenian (Marinoan) glaciation. Previous research has highlighted a complex sedimentary architecture with evidence of subaqueous, subglacial and non‐glacial conditions. This study combines well‐established sedimentological techniques with the first sedimentological application of the anisotropy of magnetic susceptibility technique in Neoproterozoic glacial sediments, to investigate the origin and palaeoenvironmental significance of glacigenic sediments within the Wilsonbreen Formation. A range of lithofacies occurs within the succession, dominated by massive diamictites, sandstones and conglomerates. Some of these facies display evidence of primary deformation and can be grouped into a Deformed Facies Association; these are interpreted to have been formed through glacitectonic deformation in a subglacial environment. Fabric investigation reveals that this deformation was associated with glacier flow towards the north. In addition, an Undeformed Facies Association records deposition in ice‐proximal and ice‐distal subaqueous environments. Taken together with intervening non‐glacial facies, the glacigenic sediments record a series of advance–retreat cycles, with ice flow involving sliding and sediment shearing below wet‐based ice.